Efficient nickel catalyst with preferred orientation and microsphere for direct borohydride fuel cell. (5th August 2021) - Hu, Bihao; Xu, Chuanlan; Chen, Peng; Yu, Jingjing; Hu, Bingbing; Xiang, Qin; Cen, Yuan; Liu, Yuping; Yu, Danmei; Chen, Changguo
Abstract: Ni catalysts with preferred orientation and microsphere were fabricated by a facile one-step pulsed voltage electrodeposition (PVE) method, while the crystal plane orientation and catalytic activity for borohydride oxidation reaction (BOR) were researched systematically. The results indicate that adjusting pulse anode potential can effectively regulate the morphology and crystal plane preferred orientation of Ni catalysts. The optimal Ni-PVE0.15 catalyst exhibits the highest catalytic activity, stability, and fuel efficiency to BOR. The improvement of catalytic activity of Ni and fuel efficiency is attributed to the more exposure of the (220) crystal plane, which blocks the competing hydrogen evolution reaction (HER), increases the intrinsic activity of the catalytic sites to BOR, and strengthens the adsorption of escaping hydrogen to further electrooxidation. Meanwhile, the no-cracks feature of the microsphere increases the active sites and avoids the shedding of catalysts. The derived insights are important for the design of efficient nickel catalysts for practical applications of direct borohydride fuel cells. Graphical abstract: Image 1 Highlights: The microsphere Ni catalyst with a highly preferred orientation of (220) plane was prepared by pulse electrodeposition. Pulsed anode potential can control the morphology and structure of Ni. The (220) crystal plane benefits the adsorption of borohydride, capture of H2, and inhibition of HER. Ni-PVE0.15 catalyst demonstrates excellent activity to BOR with high stability and efficiency.